Alzheimer's disease in the context of social work from the perspective of family caregivers - Martina, Lacková; Lucia, Dimunová (Magyar Gerontológia, 2023)
In the context of rising quality of life and improving living conditions, as well as improving health care, people are now living to a higher age than in the past. Alzheimer's disease is the most common form of dementia in European countries. As a result of the development of the disease, individuals are often dependent on the help and care of other people, in most cases family members. This care interferes with the functioning of the family, so monitoring the needs and assistance for family members is essential.